Customer survey analysis for a keyless anti-theft bicycle lock system prototype - Ismail I.N.; Zuhair Zakariya M.A.; Azman N.S.; Zawawi M.H.; Zahari N.M.; Mahmood Zuhdi A.W.; Eqwan M.R.; Mohamed H.; Ramli M.Z.; Mansor M.H.; Syaifoelida F.; Zakaria A.A.; et al. (American Institute of Physics Inc., 2023)
Student bicycle commuters are not satisfied with the present selection of bicycle locks accessible. Many express that locking their bicycle isn't a simple procedure. User contemplates showed that u-locks are seen to be the strongest and rent powerless to breaking, anyway they are inconvenient and badly designed to utilize. Based on the literature review, benchmarking, type of lock review and survey, an idea of the market demand and also improvements that needed to be done on the existing systems to meet the needs and demands of the customer is obtained. The survey gave a clear view of the preferences and priorities of the user when it comes to lock purchasing and utilizing. Customer requirements define the qualities in the end product or system which customers seek, which in most cases is not quantifiable. Despite the case, these qualities can be translated into technical parameters or quantitative attributes via the House of Quality (HoQ). 2021 American Institute of Physics Inc.. All rights reserved.